Exploring the Simultaneous Effect of Total Ion Concentration and K:Ca:Mg Ratio of the Nutrient Solution on the Growth and Nutritional Value of Hydroponically Grown Cichorium spinosum L. - Orfeas Voutsinos-Frantzis; Georgia Ntatsi; Ioannis Karavidas; Ioannis Neofytou; Konstantinos Deriziotis; Andreas Ropokis; Beppe Benedetto Consentino; Leo Sabatino; Dimitrios Savvas (Agronomy, 2022)
Nutrient-efficient plants and agricultural systems could tackle issues resulting from conventional agriculture. Spiny chicory (Cichorium spinosum L.), a very adaptive, wild edible vegetable, is gaining commercial interest as a functional food. Floating-raft hydroponics is a method commonly used for the commercial cultivation of leafy vegetables due to numerous advantages compared to soil cultivation. In this paper, the simultaneous effects of different potassium, calcium and magnesium ratios and different electrical conductivity (EC) levels on the growth and mineral composition of hydroponically grown C. spinosum were investigated. Four nutrient solutions (NS) were compared, two NS with low EC (L, 2.4 dS/m) and two with high EC (H, 3.6 dS/m) with K:Ca:Mg ratios of either 50:40:10 or 40:50:10. The results showed no interactions between the two factors. No significant effects were observed on the fresh and dry weight, leaf number and leaf area. High EC levels increased the K content and decreased the Mn and Zn content in the leaf tissues. The 40:50:10 ratio led to increased Ca content in plant tissues. The Nitrate-N was only affected by the EC level and was increased under H conditions, whereas the total-N was not affected.